DNA Sequencing and Bioinformatics Analysis of Clone pOr78 from the Species Specific Suppression Subtractive Hybridization Library Constructed from Endemic Wild Rice Species O. rhizomatis - Rajkumar, Gowri; Weerasena, Jagathpriya; Fernando, Kumudu (International Journal of Applied Sciences and Biotechnology, 2017)
Oryza rhizomatis is an endemic wild rice species in Sri Lanka with some unique characteristics of biotic and abiotic stress resistance. Hence characterization of desirable novel genes found in Oryza rhizomatis will be useful for transferring traits to commercial varieties. Therefore, in this study, a species-specific cDNA library was constructed from the wild rice species O. rhizomatis to isolate and characterize novel genes which are specifically present in this species but absent in cultivated rice (Oryza sativa). Forty recombinant clones were randomly selected from the cDNA SSH library and the inserts were sequenced. Sequence analysis of all forty clones indicated that the suppression and hybridization procedures in the library construction were successful as most of the clones have significant alignment with other wild rice species than O. sativa used as a reference cDNA for construction of subtraction library in this study. Therefore the genes which were specifically expressed in the wild rice species O. rhizomatis enriched in the SSH library. From this study it was possible to characterize O. rhizomatis nsLTP1 proteins (non specific Lipid Transfer Protein 1) super family AAI_LTSS which are found to be involved in control of pathogen attack related responses in plants. Int. J. Appl. Sci. Biotechnol. Vol 5(2): 133-140